The effect of spatial correlation of sea states on extreme wave loads of ships. (18th August 2021) - Mikulić, Antonio; Katalinić, Marko; Ćorak, Maro; Parunov, Joško
ABSTRACT: The purpose of the study is to include a spatial statistical correlation between sea states that ship encounters during a voyage to improve wave scatter diagram for the analysis of ship structures. The methodology consists of computation of system reliability of a series of partially correlated events, representing sea states that ship encounters along the sailing route. The North Atlantic wave scatter diagram is modified to account for such spatial correlation and new scatter diagrams for partially correlated sea states are constructed. Based on such "correlated scatter diagrams", long-term distribution of vertical wave bending moments is performed and compared to the results following from an "uncorrelated scatter diagram". It was found that a spatial correlation may considerably reduce extreme vertical wave bending moments. Verification of the methodology is performed by simulating shipping route in the North Atlantic using ERA5 wave database.